Depresión en paciente diagnosticada con cáncer cervicouterino y su afección en la conducta - Rivera Ulloa, Eliana Katherine (2016)
This research aims to explain the development of depression in a patient diagnosed with cervical cancer and its behavioral affection based on the Cognitive Behavioral Psychological Approach, the study describes each of the characteristics of the emotional state of a cancer patient after receiving The medical diagnosis, the development of depression depends on the accumulation of experiences in the person, if their experiences have been unpleasant and the feeling added to the events has been equal the greater the risk of suffering from depression, it is normal for a cancer patient The cancer modifies the life of the person who suffers it, its contexts are altered and it is forced to adapt to these situations, but the severity and the duration of the symptoms will be governed by the emotional value that it gives to these events , Deferring plans, changing or eliminating them from the patient's life generates a daunting worldview, not knowing what will happen in the course of the illness saddens the person and his family, his affective tone declines and the symptoms of Depression, sadness, loneliness, guilt, discouragement, self, aggression, isolation, suicidal thoughts and suicidal acts, these symptoms cause inactivity in the person, their behavior is altered and does not act as they used to do before diagnosis.